2013
DOI: 10.1002/jobm.201200606
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of a polygalacturonase gene of Ustilago maydis and characterization of the encoded enzyme

Abstract: Ustilago maydis is a pathogenic fungus that produces the corn smut. It is a biotrophic parasite that depends on living plant tissues for its proliferation and development. Polygalacturonases are secreted by pathogens to solubilize the plant cell-wall and are required for pathogen virulence. In this paper, we report the isolation of a U. maydis polygalacturonase gene (Pgu1) and the functional and structural characterization of the encoded enzyme. The U. maydis Pgu1 gene is expressed when the fungus is grown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 52 publications
0
4
1
1
Order By: Relevance
“…This behavior is contradictory to previous reports of the yeast-like growing AB33 progenitor strain FB2 that was able to metabolize polygalacturonic acid [23]. Other reports clearly attribute CAZyme expression to the plant invasive, filamentous growth form that was not part of this study [24, 41]. Differences between the studies might occur from different medium composition, substrate suppliers or cultivation conditions and are currently under investigation.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…This behavior is contradictory to previous reports of the yeast-like growing AB33 progenitor strain FB2 that was able to metabolize polygalacturonic acid [23]. Other reports clearly attribute CAZyme expression to the plant invasive, filamentous growth form that was not part of this study [24, 41]. Differences between the studies might occur from different medium composition, substrate suppliers or cultivation conditions and are currently under investigation.…”
Section: Resultscontrasting
confidence: 99%
“…Few pectinolytic enzymes (including endo-polygalacturonase, pectin lyase and pectin methylesterase) have been annotated in the U. maydis genome [16, 24]. Polygalacturonic acid could act as a model substrate in this context as it shows, compared to homogalacturonan or pectin, a good accessibility for degradation into monomeric galacturonic acid by endo- or exo-polygalacturonases [41].…”
Section: Introductionmentioning
confidence: 99%
“…The K m values of most of the microbial PGs are in the range of 0.1-5.0 (Polizeli et al 1991;Zhang et al 1999;Niture et al 2001;Singh and Rao 2002;Thakur et al 2010a, b;Yadav et al 2012;Martins et al 2013;Chen et al 2014). An exo-PG from the fungus Penicillium frequentans has very low K m value of 0.059 (Barense et al 2001) while PG from pathogenic fungus Ustilago maydis revealed comparatively very high K m of 57.84 (Castruita-Domínguez et al 2014). The catalytic rate constant k cat of purified PG was found to be 194 s -1 which is higher than k cat values of 90 and 70 s -1 for endo-PGs from Aspergillus japonicus and Fusarium moniliforme (Semenova et al 2003;Niture et al 2001).…”
Section: Kinetic Parametersmentioning
confidence: 99%
“…2 d). Optimum temperature of 34 °C has been reported for endo-PG from pathogenic fungus Ustilago maydis (Castruita-Domínguez et al 2014 ). Similar temperature optimum of 30 °C has been reported for exo-PG from Paecilomyces variotii (Patil et al 2012 ).…”
Section: Resultsmentioning
confidence: 99%
“…The pH optima of purified PGs determines its possible application like fruit juice clarification, retting of natural fibers etc. It has been observed that most of the fungal PGs have pH optima 3–6 (Patil et al 2012 ; Yadav et al 2012 ; Kant et al 2013 ; Martins et al 2013 ; Castruita-Domínguez et al 2014 ; Ortega et al 2014 ; Chen et al 2014 ; Zhou et al 2015 ; Zaslona and Trusek-Holownia 2015 ; Pan et al 2015 ).…”
Section: Introductionmentioning
confidence: 99%